Prove that f(x) the inverse function of g(x) where f(x)= - 3x–6 and g(x)= - x/3–2

f(x) and g(x) are inverse functions when the following equations are true:f(g(x))=x
g(f(x))=xTo find (f(g)(x)) or (g(f(x)), use the inner function as the input for the outer function.
f(g(x))=-3((-x/3-2))-6 = x
g(f(x))= (-(-3x-6)/3)-2 = x, hence  f and g are inverse functions


Answered by Sheela K. Maths tutor

2797 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

By first proving that sin2θ=2sinθcosθ, calculate ∫1+sinθcosθ dθ.


The curve C has equation 2yx^2 + 2x + 4y - cos(πy) = 45. Using implicit differentiation, find dy/dx in terms of x and y


An object of mass 2kg is placed on a smooth plane which is inclined at an angle of 30 degrees from the ground. Calculate the acceleration of the object.


Find the co ordinates and nature of the turning points of the curve C withe equation, y=2x^3-5x^2-4x+2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences